2012
DOI: 10.1002/j.1532-2149.2012.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain coping and acceptance as longitudinal predictors of health‐related quality of life among people with haemophilia‐related joint pain

Abstract: Initially high levels of passive coping may be an obstacle to improving mental quality of life. Acceptance rather than coping may be a more useful behavioural change target, but more research is needed about the meanings and therapeutic implications of different elements of pain acceptance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 33 publications
(41 reference statements)
4
44
1
Order By: Relevance
“…In this scope, psychological interventions are effective in fostering adaptive pain coping strategies, namely through specific cognitive techniques, such as cognitive restructuring, aiming to decrease pain intensity and perception of interference . This corroborates previous findings among PWH, wherein the association between pain cognitions and emotional well‐being is emphasized, namely the effect of pain reinterpreting techniques in pain management . Other strategies, such as relaxation, hypnosis and imagery training have been related to improved pain reports and reduced analgesic intake in former studies conducted among PWH .…”
Section: Discussionsupporting
confidence: 85%
“…In this scope, psychological interventions are effective in fostering adaptive pain coping strategies, namely through specific cognitive techniques, such as cognitive restructuring, aiming to decrease pain intensity and perception of interference . This corroborates previous findings among PWH, wherein the association between pain cognitions and emotional well‐being is emphasized, namely the effect of pain reinterpreting techniques in pain management . Other strategies, such as relaxation, hypnosis and imagery training have been related to improved pain reports and reduced analgesic intake in former studies conducted among PWH .…”
Section: Discussionsupporting
confidence: 85%
“…Witkop et al demonstrated that one third of PWH report that pain impairs the ability to form close relationships and that nearly half of young adults with a bleeding disorder report being diagnosed with anxiety or depression [37]. It has been suggested that, in addition to emphasizing prophylaxis, interventions to promote acceptance of pain and to reduce negative thoughts about pain should be utilized when approaching PWH [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that better acceptance is directly related with a higher level of HRQoL. For example, in patients with hemophilia-related joint pain, pain acceptance and HRQoL were correlated and increased pain acceptance was related with higher HRQoL at follow-up (Elander et al, 2012). Also, in people with diabetes, HRQoL was strongly related to their levels of illness acceptance (Lewko et al, 2007).…”
Section: Discussionmentioning
confidence: 99%